Mechanisms Driving Macrophage Diversity and Specialization in Distinct Tumor Microenvironments and Parallelisms with Other Tissues - Van Overmeire, Eva; Laoui, Damya; Keirsse, Jiri; Van Ginderachter, Jo A.; Sarukhan, Adelaida (Frontiers in Immunology, 2014)
Macrophages are extremely versatile cells that adopt a distinct phenotype in response to a changing microenvironment. Consequently, macrophages are involved in diverse functions, ranging from organogenesis and tissue homeostasis to recognition and destruction of invading pathogens. In cancer, tumor-associated macrophages (TAM) often contribute to tumor progression by increasing cancer cell migration and invasiveness, stimulating angiogenesis, and suppressing anti-tumor immunity. Accumulating evidence suggests that these different functions could be exerted by specialized TAM subpopulations. Here, we discuss the potential underlying mechanisms regulating TAM specialization and elaborate on TAM heterogeneity in terms of their ontogeny, activation state and intratumoral localization. In addition, parallels are drawn between TAM and macrophages in other tissues. Together, a better understanding of TAM diversity could provide a rationale for novel strategies aimed at targeting the most potent tumor-supporting macrophages.